Pelatihan LINTAH (Lilin Aromaterapi dari Jelantah) di Desa Sumberdadi sebagai Inisiatif Menuju Desa Ramah Lingkungan - Ivantri, Rohmah; Maghfuri, Farhan; Jawara, Surya; Brillyan Nur; Fatimah, Delima Puteri (LP2M IAIN Sultan Amai Gorontalo, 2025)
Abstract: The LINTAH (Aromatherapy Candles from Used Cooking Oil) training was conducted in response to the problem of household used cooking oil waste that is often disposed of without being processed. The background of this activity stems from the need of the community in Sumberdadi Village to find a creative solution that is not only environmentally friendly but also economically viable. The primary objective of the training is to equip the village women's group with the skills to process used cooking oil waste into aromatherapy candles that have market potential while also promoting productive consumption patterns. The method used is based on Asset-Based Community Development (ABCD) combined with a project-based learning approach. Participants not only received theoretical explanations but also directly practiced the production process, from oil filtration, mixing aromatherapy ingredients, to candle molding. Evaluation was conducted through participatory observation, interviews, and group discussions during the reflection phase. The results of the activity showed a significant increase in participants' knowledge and skills, particularly regarding the utilization of waste as an economically valuable resource. Participants reported gaining meaningful learning experiences, where hands-on practice strengthened understanding compared to conventional learning. Additionally, a paradigm shift was observed, where used cooking oil is no longer merely waste but a productive asset that can support the circular economy and environmental sustainability.